Survey of factors affecting religious beliefs in physical education students - Mohammadbagher Forghani Ozrudı; Somayeh Rahimi Alıabadı (Selcuk University, 2016)
This survey was performed in order to Factors affecting religious beliefs in physical education students with sub-purpose of the impact of family, university environment, instructors' educational method, university teachers' performance, and community. The survey method was a cross-sectional survey type, and the statistical population included all university teachers of Islamic Azad University, Sama unit, the number of which was 1316 people, and the statistical sample volume was 297 people which were determined based on various educational bases by stratified random sampling by using table of Morgan. The tool of survey was questionnaire depending on response surveyor made, based on Likert's design. Its validity and reliability was obtained (α=0.82) by using Cronbach Alpha test. The results showed that the impact of family, University environment, instructors' educational method, University teachers' performance, and community may greatly affect the internalization of religious values in students.